Knowledge, Attitude, and Practice of the Interns About Exfoliative Cytology in a Tertiary Care Dental Hospital in Bhubaneswar City: A Questionnaire-Based Survey - Chakraborty Sankha S; Manohar Balaji; Shroff Yashshwini; Mahapatra Niva; Kaur Awneet (Wolters Kluwer Medknow Publications, 2024)
The most significant accomplishment of dentists is the early detection of oral dysplasia or the rapid diagnosis of potentially malignant lesions. An additional test that assists in the diagnosis of numerous oral illnesses is exfoliative cytology. This study was conducted among dental professionals in the city of Bhubaneswar to assess their exfoliative cytology knowledge, attitudes, and practices. Fifty-eight dental interns participated in a cross-sectional, descriptive, Web-based questionnaire study. The findings reveal that while some interns were knowledgeable about some components of exfoliative cytology in oral cancer (OC) screening, they lacked a thorough understanding of other crucial elements. To enhance early diagnosis and lessen the prevalence of OC, it is critical that dental practitioners increase their understanding of and use of exfoliative cytology. To address the misconcepts found in the study, it draws attention to the necessity of patient education and public awareness campaigns. The study recommends more awareness and education among dental practitioners and emphasizes the need of tackling OC through preventive measures and appropriate diagnostic techniques such as exfoliative cytology.